Health professionals' willingness to pay and associated factors for cervical cancer screening program at College of Medicine and Health Sciences, University of Gondar, Northwest Ethiopia. - Abebe Ayinalem Tarekegn; Mezgebu Yitayal Mengistu; Tsega Hagos Mirach (PLoS ONE, 2019)
Introduction Cervical cancer is a major public health problem in developing countries like Ethiopia. Cervical cancer screening service has been offered to high-risk groups in Ethiopia since 2013. However, there is no evidence on the willingness to pay for the screening. Therefore, we conducted this study to assess the female health professionals' willingness to pay for cervical cancer screening at the College of Medicine and Health Sciences, University of Gondar, Northwest Ethiopia. Methods Institutional based cross-sectional study design was used to assess the health professionals' willingness to pay for the cervical screening from March to April, 2018. Simple random sampling technique was used to select study participants from a list of female health professionals who has been working for the College of Medicine and Health Sciences, University of Gondar. The data were entered into EpiData version 3.1 and exported to STATA version 14 for analysis. Tobit models were used to identify factors which had statistical significant association with willingness to pay for cervical cancer screening service. Results A total of 392 respondents participated in the study with a response rate of 92.7%. The majority (83.4%) of participants were willing to pay for cervical cancer screening. The average amount of money they were willing to pay was ETB 194.7 (US$7.16) per service. Age ≥ 30 years, educational status, perceived seriousness of cervical cancer, perceived quality of cervical cancer screening service and monthly income were significantly associated with willingness to pay for cervical cancer screening. Conclusion High proportion of study participants were willing to pay for cervical cancer screening. Therefore, the policy makers can scale-up cervical cancer screening by setting appropriate fee for service charge. They can also raise awareness of cervical cancer and offer quality service in order to increase the benefits of the program.